Risk factors for osteoporosis in postmenopausal women from Guadalajara, Jalisco - Anahí González-Mercado; j Yoaly Sánchez-López; Bertha Ibarra Ibarra (Instituto Nacional de Salud Pública, 2013)
Objective. To know risk factors and the frequency of osteoporosis (OP) in postmenopausal women. Materials and methods. Bone mineral density was measured in lumbar spine of 513 postmenopausal women from a hospital of Guadalajara, Jalisco during 2007-2008. The cutoff points of the associated variables were obtained by ROC curves and odds ratio (OR) by logistic regression. Results. The 25.2% (95%CI 21.44-28.96) of the women was OP. The variables associated with OP and cutoff points were age mayor que 60 years, weight menor que 71kg, height menor que 1.54m and BMI menor que 29.2kg/m2, with OR greater than 3.19 (p menor que 0.0001). Conclusions. It is recommended setting cutoff points to estimate risk factors for OP more accurately in each population.